Vitrified oocyte donation to a Turner’s syndrome patient - Escudero Díaz, Francisco (2015)
Turner syndrome is a chromosome aberration with complete or partial loss of one of the sexual chromosomes. Classical characteristics are short stature and ovarian failure due to dysgenesia. Oocyte donation has made possible gestation in Turner’s patients but resulting in high maternal mortality due to rupture of the aorta or hypertensive disorders. The case of a Turner syndrome patient resulting in multiple pregnancy in a vitrified oocyte donor program is presented.